The work process and care production in a Brazilian indigenous health service - Aridiane Alves Ribeiro; Giovanni Gurgel Aciole; Cássia Irene Spinelli Arantes; Jeff Reading; Donna L.M. Kurtz; Lídia Aparecida Rossi (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To understand the constitutive elements of the work process and care production in an Indigenous Health Support Service. Methods: Case study. Systematic observation and semi-structured interviews were conducted in January and February of 2012. The participants were 10 nursing professionals of an Indigenous Health Support Center, located in Mato Grosso do Sul state, Brazil. The work process was used as a conceptual and analytical category. Results: Through interpretative analysis, the data were organized into three categories. The results showed that care production was focused on procedures and guided by rigid institutional rules and bureaucracy. The prioritization of institutional rules and procedures was detrimental to the provision of person-centered care. Conclusion: The temporary employment contracts and rigid bureaucratic organization generated a tense work environment. These aspects do not maximize the efforts of the nursing staff to provide person-centered care.